Major elements geochemistry of chlorite in different ore deposits and its genesis and exploration significance: a case study from Naruo porphyry Cu deposit in Duolong ore district, Tibet - Li, Faqiao; Tang, Juxing; Song, Yang; Li, She; Tang, Pan; Li, Haifeng; Yang, Huanhuan; Wang, Qin; Wang, Yongqiang; Danzeng, Zongzhui; Li, Yanbo; Li, Jianli; et al. (Frontiers in Earth Science, 2024)
Chlorite is present extensively in many types of deposits. The mechanism underlying the chemical variations in chlorite remains unclear. The Naruo porphyry deposit is a giant copper porphyry deposit in the Duolong ore district of Tibet. Chlorite, which is abundant in this deposit, has yet to be studied systematically; hence, we used principal component analysis (PCA) to assess the correlation between chlorite elements and various types of mineral deposits. We then conducted a preliminary investigation into its mineralogy and geochemistry to better understand its formation process and identify potential prospecting indicators. The PCA method proved effective in discerning two distinctive element signatures within the chlorite and categorising them into four deposit types: orogenic Au deposits, granite-type U deposits, and skarn-type Sn deposits that exhibit high FeO and low MgO distinguishing them from porphyry copper deposits. The chlorite in the Naruo deposit is classified as either early metasomatic (M-type), consisting mainly of clinochlore, or late hydrothermal (H-type), primarily consisting of clinochlore and chamosite. This classification suggests that H-type chlorite formed in a reductive environment conducive to Cu precipitation at medium temperatures (255°C–342°C). Al-Si and Fe-Mg substitutions were found to be the primary processes involved in its generation. Additionally, from the mineralisation centre outwards, there was an observed decrease in Si content as well as the Fe/(Fe+Mg) ratio in H-type chlorite, along with decreases in temperature, sulphur, and oxygen fugacity of all chlorites; conversely, increases were observed for Al content along with Mg and Mn elements in H-type chlorite. Chlorite is useful for exploring porphyry copper systems as an indicator mineral.